2002
DOI: 10.1021/cm0211599
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Based Synthesis of Monodisperse Rare-Earth-Doped Colloidal SiO2 Spheres

Abstract: Rare-earth-doped SiO2 colloids can be grown in a wet chemical procedure by adding the appropriate rare earth chloride to a solution of tetraethoxysilane, glacial acetic acid, and water. The size polydispersity of the particles can be controlled in a seeded growth process, and monodisperse Er3+-doped particles were grown by covering 183-nm-diameter seed particles with a 5−6-nm-thick (Er-doped) shell. After annealing, typical Er luminescence is observed with long luminescence lifetimes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 18 publications
4
30
0
Order By: Relevance
“…As may be expected, the particle size will be strongly influenced by ratio of cosurfactant to surfactant, the ratio of surfactant to oil, and the ratio of water to oil [50]. The experimental result suggested that when the ratio of cosurfactant to surfactant and the ratio of surfactant to oil are kept fixed the ratio of water to oil can be carefully adjusted to control the particle size [51]. The inverse microemulsion method yielded uniform RuDT nanoparticles.…”
Section: Preparation Of the Modified Electrodementioning
confidence: 70%
“…As may be expected, the particle size will be strongly influenced by ratio of cosurfactant to surfactant, the ratio of surfactant to oil, and the ratio of water to oil [50]. The experimental result suggested that when the ratio of cosurfactant to surfactant and the ratio of surfactant to oil are kept fixed the ratio of water to oil can be carefully adjusted to control the particle size [51]. The inverse microemulsion method yielded uniform RuDT nanoparticles.…”
Section: Preparation Of the Modified Electrodementioning
confidence: 70%
“…This method cannot be used if one wants to incorporate rare earths into the glass, because lanthanide salts form insoluble lanthanide hydroxides in basic environments. The problem, however, may be overcome by using acid catalysts [63,64]: in this case one obtains silica microspheres with different diameters, ranging from a hundred nanometers to approximately 150 micrometers, always with a very high surface quality, as shown by the TEM images in Fig. 6.…”
Section: Sol-gel Processesmentioning
confidence: 99%
“…These ions can be obtained from their salts (like europium from its nitrate) to outwardly impregnate assembled opals, [207] or can be integrated in the opal spheres adding rare earth salt (like erbium from its chloride) at the time of synthesis. [208] Alternatively, fluorescent erbium-doped titania nanoparticles can be synthesized through a sol±gel process followed by peptization and hydrothermal treatment [209] that can, subsequently, be used to infiltrate previously assembled opals. Magnetic materials have been introduced in opals not only but mostly for the magneto-optical properties they develop in this periodic environment.…”
Section: Infiltrated Opalsmentioning
confidence: 99%